2019
DOI: 10.4102/curationis.v42i1.1849
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of primary healthcare nurses regarding the integration of HIV and AIDS services into primary healthcare in Vhembe district of Limpopo province, South Africa

Abstract: Background: Integration of human immunodeficiency virus and acquired immune deficiency syndrome (HIV and AIDS) services into primary healthcare (PHC) is a key public health approach to achieving universal access to antiretroviral therapy (ART). Despite the government’s efforts of integrating HIV services into PHC, an insufficient number of PHC staff and inadequate infrastructure are challenging when integrating HIV and AIDS services into PHC. This study explored the challenges of PHC nurses regarding the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…14 Previous studies in South Africa have shown that the primary healthcare clinics are insufficiently staffed. 14,16 Similar observations have been reported in Europe and Tanzania where availability of staff, services provided and reliable access to medication were significant contributors to patients' choice of healthcare facility. 5,6 In the province of Tehran in the Islamic Republic of Iran, it was reported that structural indicators contribute highly in attracting patients to a healthcare facility.…”
Section: Discussionsupporting
confidence: 68%
“…14 Previous studies in South Africa have shown that the primary healthcare clinics are insufficiently staffed. 14,16 Similar observations have been reported in Europe and Tanzania where availability of staff, services provided and reliable access to medication were significant contributors to patients' choice of healthcare facility. 5,6 In the province of Tehran in the Islamic Republic of Iran, it was reported that structural indicators contribute highly in attracting patients to a healthcare facility.…”
Section: Discussionsupporting
confidence: 68%
“…Government clinics already have a heavy influx of patients and long queues. A qualitative study in South Africa reported as long as nurses are expected to manage large number of patients each day in primary care, HIV and AIDS services are unlikely to be successfully integrated into PHC, as inadequate staffing and healthcare facility space will negatively impact service delivery [50]. This is especially true in countries like South Africa, which are implementing Universal Test and Treat and same-day initiation policies.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the AIDS epidemic in South Africa is reflected in the dramatic change in mortality rates. According to Tshililo et al (2019), RNs at clinics and health centres face challenges when they come across patients who do not accept their HIV-positive status. Some patients become frustrated after they are told of their HIV-positive status and this interferes with the process of HIV/AIDS service integration.…”
Section: Introductionmentioning
confidence: 99%
“…The client-centred nature of counselling engenders trust between the counsellor and the client so that there is an opportunity for in-depth discussion of HIV/AIDS, including how to prevent infection. The RNs who participated in the study explained that integrating HIV services into PHC increases their workload which has a negative impact on service delivery; they also indicated that the integration of HIV and AIDS services is time-consuming as they tend to spend too much time with one patient especially newly diagnosed patients (Tshililo et al 2019).…”
Section: Introductionmentioning
confidence: 99%